2006
DOI: 10.1111/j.1440-1754.2006.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitudes to the identification of their infants as carriers of cystic fibrosis by newborn screening

Abstract: Although the NBS process for CF in Victoria is working efficiently for the majority of families whose infant is identified as a carrier there are areas that can be improved. We recommend that greater attention should be given to informing parents that a consequence of NBS is CF carrier detection and strategies to improve utilisation of cascade testing should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 16 publications
5
74
1
Order By: Relevance
“…15 While another found residual anxiety among some parents about their child's health and reproductive decisions 6 years after being informed of newborn CF carrier status. 63 This suggests that some parents' information and support needs may not be met. There has been less empirical work conducted with parents of SC carriers following newborn screening but counselling has been advocated, 86 without which it has been suggested results may cause undue anxiety and parents may fail to appreciate the implications of the results.…”
Section: Anxiety and Understanding Following Carrier Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 While another found residual anxiety among some parents about their child's health and reproductive decisions 6 years after being informed of newborn CF carrier status. 63 This suggests that some parents' information and support needs may not be met. There has been less empirical work conducted with parents of SC carriers following newborn screening but counselling has been advocated, 86 without which it has been suggested results may cause undue anxiety and parents may fail to appreciate the implications of the results.…”
Section: Anxiety and Understanding Following Carrier Resultsmentioning
confidence: 99%
“…57 Research with parents following newborn screening supports disclosure of newborn carrier status. 13,15,[57][58][59][60] However, there is commonly inconsistency in whether specific communication protocols are in place for SC or CF carrier results, 37,[61][62][63] and further research is required into parents' experiences or understanding of such communication 13 and the most effective and acceptable communication models. 8 There remains little guidance on the most appropriate ways to convey carrier status results, 8,41 or research on parents' experiences of receiving carrier results to inform approaches.…”
Section: Summary Of Current Evidencementioning
confidence: 99%
“…15 This is less commonly documented in the literature and the outcome of communication is often defined by the number of at-risk family members that contact the genetic services. 9 The frequency of contact is estimated to be between 20 and 40%, 18,19 and whereas barriers and facilitators to communication are well documented, 20 -24 the reason at-risk family members do not contact the genetic services is largely unknown. Exploration of families' experiences may further illuminate the process of communicating genetic information and provide evidence-based information for health professionals involved in the provision of genetic services.…”
Section: Introductionmentioning
confidence: 99%
“…10,33,36,45 A minority of parents continued to think about the test results, 36 worry about the child's health, or remain anxious. 33 One study found that parents of children with false-positive results were more stressed and their relationship with their child more dysfunctional than parents who had children with normal test results. 47 Most studies, however, found little long-term difference in parental depression, 45 anxiety, well-being, or rejection or protection between parents of children with false-positive results and those of children with normal results.…”
Section: Religious Faithmentioning
confidence: 99%